The analysis of speech act in Thor: Ragnarok - Putri, Erna Pranata (LADU: Journal of Languages and Education, 2021)
Background: Â People attempt to express themselves by producing utterances. The utterances do not only contain grammatical structures and words but people also perform actions through the utterances. In producing an utterance, the speaker regularly anticipates the hearer to recognize his/her intention. The study that covers this is speech act.Purpose: This research attempted to analyse the classification of speech acts proposed by Searle, namely representatives, directives, expressives, commissives, and declaraions in the movie script of Thor: Ragnarok.Design and methods: A qualitative method was used in this research. The object of this study is the movie script of Thor: Ragnarok.Results: The result showed that there are 189 data included in the category Representative which covers 38% out of the total data, 183 data included in the category Directive which covers 37% out of the total data, 77 data included in the category Expressive which covers 15% out of the total data, 50 data included in the category Expressive which covers 10% out of the total data, and 2 data included in the category Declarations.